Interest in Sociology Learning of High School Students during the Process of Learning Activities - Ega, Fresensia; Rustiyarso, Rustiyarso; Al Hidayah, Riama (Universitas Tanjungpura, 2024)
This study aims to determine students' interest in learning sociology at SMA Negeri 2 Nanga Pinoh during classroom learning activities. The research adopts a qualitative approach using descriptive research methods. Data for this study were collected from teachers and students. The data collection focused on the interest of eleventh-grade of social students in studying sociology during classroom learning activities. The findings reveal that the overall interest of eleventh-grade social class students in Nanga Pinoh is relatively high. It is supported by the students' personal and psychological interests, as evidenced by their diligent submission of assignments, high attendance, and positive engagement in learning activities, reflecting a sense of enjoyment. However, students' participation and attention during learning activities are still lacking when considering situational interest. It is evident from their relatively low participation and engagement in classroom activities. Keywords: Interest in Learning, Students, During the Learning Process